Exploring socio-demographic determinants of breast self-examination practices among Jordanian women: insights from the 2023 population-based survey - Amr Ahmed Aly Ibrahim; Moaz Yasser Darwish; Sara Hosny El-Farargy; Nour Eldein Saad; Aya Khafage; Mahmoud Shaaban Abdelgalil (PLoS ONE, 2026)
Background Breast cancer is the most prevalent cancer and the leading cause of cancer-related deaths among Jordanian women. Breast self-examination (BSE) plays a vital role in the early detection of breast cancer, improving survival rates. Despite its proven benefits, BSE remains underutilized in Jordan. This study aimed to explore the factors influencing BSE practices among married Jordanian women aged 20–49 years, utilizing data from the Jordan Population and Family Health Survey (JPFHS). Methods The study analyzed data from the 2023 JPFHS, encompassing a representative sample of 12,595 Jordanian women aged 15–49. The study examined various socioeconomic, demographic, behavioral, and geographic variables. Socioeconomic and demographic factors included age, education level, wealth index, employment status, marital status, parity, and current pregnancy status. Behavioral factors encompassed smoking frequency and media consumption habits, such as internet use, the frequency of watching television, listening to the radio, and reading newspapers or magazines. Geographic variables included the type of residence (urban or rural) and the governorates where participants lived. Associations between these variables and BSE were assessed using multivariable logistic regression. Results Among the 12,304 married women included in the analysis, 9,851 women reported not performing BSE, while 2,453 women indicated that they had. Multivariate analysis revealed that significantly better BSE practice was observed among older women (e.g., age 45–49 vs 20–24: AOR 3.08, p < 0.001), those with higher education levels (e.g., secondary vs no education: AOR 2.41, p = 0.027), and wealthier women (e.g., richest vs poorest: AOR 1.54, p = 0.023). Additionally, multiparous women, daily smokers, and women with frequent internet use and frequent reading of newspapers or magazines were also more likely to practice BSE. Regional differences showed that women in Ajloun, Aqaba, and Balqa were more likely to perform BSE, while women in Irbid and Mafraq had lower rates of BSE practice. Conclusion To improve BSE rates among married women in Jordan, targeted health campaigns should focus on younger, less educated, and economically disadvantaged women, particularly in Irbid and Mafraq. Culturally sensitive education, digital platforms, and community outreach can raise awareness and address barriers like stigma and misconceptions, promoting proactive breast health practices nationwide. Future researchers are encouraged to further investigate cultural barriers toward BSE.